PROBLEMATIKA GURU DALAM MEMBINA AKHLAK SISWA DI MTS SWASTA IRA MEDAN - Nelliana Pohan; Afrahul Fadhila Daulai (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to identify and analyze the various problems faced by teachers in fostering student morals at Madrasah Tsanawiyah Swasta Ira Medan. This research is a qualitative research with descriptive approach. In this research, the subjects are the head of Madrasah, teachers, and students. Data collection techniques used in this research are interviews, observations, and documentation studies. Data analysis techniques used in this research are the reduction stage, data presentation stage, and conclusion drawing. The results showed that some of the main challenges faced by teachers include external and internal factors, external factors, namely the lack of parental upbringing, the negative influence of the social environment, the influence of peer association while internal factors are innate factors, or habits in everyday life. So that teachers must have methods in fostering student morals such as, (1) exemplary method (uswatun hasanah), (2) habituation method, (3) advice method. And the solution to the teacher's problem in fostering student morals is (1) giving a good example as a teacher or a good example, (2) giving advice to students (3) good communication between teachers, parents, and students, and others.